Hubungan penggunaan kb suntik dmpa dengan gangguan menstruasi pada ibu pus di wilayah kerja puskesmas ngaglik ii sleman yogyakarta : The correlation of dmpa contraceptive injection with menstrual disorders in mothers fertile couple in the work area of public health center ngaglik ii sleman yogyakarta - Utami Lubis, Dina Putri (Stikes Wira Medika Bali, 2021)
Background: Fertility or birth is one of the factors causing the increase in population. The Indonesian government implements a program to address this problem, namely the Family Planning program. The most widely used contraceptive method in the Special Region of Yogyakarta is injection method and Sleman Regency has the highest number of contraceptive injection users in Yogyakarta. The most widely used type of contraceptive injection is Depo-Medroxy-Progesterone Acetat (DMPA) and its use turns out to have side effects, one of which is menstrual disorders. Objective: To determine the correlation between the use of DMPA contraceptive injection and menstrual disorders in women in the working area of the Ngaglik II Public Health Center, Sleman, Yogyakarta. Methods: This type of research is a type of quantitative research that is descriptive correlational using a cross sectional approach. The population in this study were fertile couple who used contraceptive injection in the work area of the Ngaglik II Health Center. In August 2018-January 2019 there were 480 family planning acceptors. The sampling technique is purposive sampling. Results: There was a correlation between variables by looking at the continuity correction value of 37,820 which means that the value of x2 count (37,820) is greater than x2 table (3,481). Conclusion: There is a significant relationship between the use of DMPA injectable contraception and Menstrual Disorders in EFA mothers in the working area of the Ngaglik 2 Public Health Center, Sleman Yogyakarta.